The importance of colonization pressure in multiresistant Acinetobacter baumannii acquisition in a Greek intensive care unit - Arvaniti, Kostoula (BioMed Central, 2012)
INTRODUCTION: We investigated the role of colonization pressure on multiresistant Acinetobacter baumannii acquisition and defined patient-related predictors for carriage at admission and acquisition during hospitalization in intensive care unit (ICU) patients. METHODS: This was a 12-month, prospective, cohort study of all patients admitted to a single ICU of a tertiary hospital. Screening samples were collected at ICU admission to identify imported carriers, and weekly during hospitalization to identify acquisition. Colonization pressure (carriers' patient-days × 100/all patients' patient-days) and the absolute number of carriers were calculated weekly, and the statistical correlation between these parameters and acquisition was explored. Multivariable analysis was performed to identify predictors for A. baumannii carriage at admission and acquisition during hospitalization. A. baumannii isolates were genotyped by repetitive-extragenic-palindromic polymerase chain reaction (PCR; rep-PCR). RESULTS: At ICU admission, 284 patients were screened for carriage. A. baumannii was imported in 16 patients (5.6%), and acquisition occurred in 32 patients (15.7%). Acquisition was significantly correlated to weekly colonization pressure (correlation coefficient, 0.379; P = 0.004) and to the number of carriers per week (correlation coefficient, 0.499; P <0.001). More than one carrier per week significantly increased acquisition risk (two to three carriers, odds ratio (OR), 12.66; P = 0.028; more than four carriers, OR, 25.33; P = 0.004). Predictors of carriage at admission were infection at admission (OR, 11.03; confidence interval (CI), 3.56 to 34.18; P < 0.01) and hospitalization days before ICU (OR, 1.09; CI, 1.01 to 1.16; P = 0.02). Predictors of acquisition were a medical reason for ICU admission (OR, 5.11; CI, 1.31 to 19.93; P = 0.02), duration of antibiotic administration in the unit (OR, 1.24; CI, 1.12 to 1.38; P < 0.001), and duration of mechanical ventilation (OR, 1.08; CI, 1.04 to 1.13; P = 0.001). All strains were multiresistant. Rep-PCR analysis showed one dominant cluster. CONCLUSIONS: Acquisition of multiresistant A. baumannii in ICU patients is strongly correlated to colonization pressure. High levels of colonization pressure and more than two carriers per week independently increase acquisition risk. Patient-related factors, such as infection at admission and long hospitalization before the ICU, can identify imported A. baumannii carriers. Medical patients with extended administration of antibiotics and long duration of mechanical ventilation in the ICU were the most vulnerable to acquisition.